Covalently conjugated transforming growth factor-β1 in modular chitosan hydrogels for the effective treatment of articular cartilage defects1. (21st May 2015) - Choi, Bogyu; Kim, Soyon; Fan, Jiabing; Kowalski, Tomasz; Petrigliano, Frank; Evseenko, Denis; Lee, Min
<x xml:space="preserve">Abstract</x> We developed strategies to stabilize TGF-β1 signaling in visible blue-light inducible chitosan hydrogel systems for specific use in cartilage regeneration.